Modelagem de projeç\~ao de tráfego e simulaç\~ao de impactos de regras de compartilhamento de risco de demanda para o desempenho de concess\~oes rodoviárias no Brasil: Estudo para a BR-040 - Dianifer Leal Borges; Edison Benedito da Silva Filho; Levy Cunha Bravo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The objective of this study is to evaluate the costs and benefits of different demand risk sharing rules for road infrastructure concessions, from the point of view of the economic attractiveness of the projects for the concessionaire and the price reduction for users. The traffic trajectory of a highway is simulated using a stochastic model of Brownian Geometric Movement, using data and parameters from the BR 040 concession auction. From this forecasting, the impacts of different models of demand risk sharing rules on the financial structure of projects are evaluated. We shall demonstrate the superiority of these models over the one without risk sharing in order to increase the financial viability of projects and the potential for reducing tariffs for users.
Keywords: C15; H43; R42; 330; stochastic models; risk sharing; infrastructure concessions